The Aesthetics of Silence in Samuel Beckett’s “Waiting for Godot” and Harold Pinter’s “The Homecoming”: Communicative Voids as Existential Expression - Abbas, Maytham Abdulrazzaq (Researchparks Publishing, 2026)
This paper introduces the significance of silence as a potent expressive tool in 20th-century drama, focusing on Samuel Beckett and Harold Pinter as key innovators within the Theatre of the Absurd. The primary goal is to conduct a comparative analysis of the aesthetics and function of silence in Beckett’s Waiting for Godot and Pinter’s The Homecoming. Drawing on theoretical frameworks from theatrical semiotics, the Theatre of the Absurd (notably Martin Esslin), and existentialist philosophy (resonating with Camus and Sartre), the study examines how both playwrights utilize communicative voids. The significance lies in demonstrating the distinct dramaturgies of silence employed: Beckett’s silence articulates metaphysical absurdity, language inadequacy, and existential solitude, confronting a silent universe, while Pinter’s silence operates strategically within social and psychological realms, revealing power dynamics, interpersonal conflict, and ambiguity through tactical pauses and subtext. The results show that Beckett’s silence embodies a metaphysical void, whereas Pinter’s reflects psychological warfare and social critique. Both transform absence into profound existential expression, highlighting different facets of the modern human condition—one cosmic, the other social—thereby enriching the understanding of silence as a versatile dramatic force.